Phytochemical evaluation and antioxidant effects of the essential oil and distillates of Nepeta crispa Willd. - Mohammad Bahramloo; Shirin Moradkhani; Mahsa Sedaghat Hamedani (Institue of Medicinal Plants, ACECR, 2023)
Background: Nepeta crispa Willd. (Lamiaceae) is a medicinal plant endemic to Iran with numerous ethnobotanical uses. Objective: The current study focuses on the quality control of N. crispa growing in Hamadan province. Methods: Hydro-distilled essential oil from aerial parts of N. crispa was obtained using the Clevenger apparatus. Four samples of N. crispa distillate were purchased from various locations. Methanol extracts from aerial parts of this plant were obtained by the maceration method. Micromorphological characteristics, antioxidant properties, and chemical constituents of N. crispa essential oil and distillates were evaluated. Determination of the total phenols and flavonoid contents of the extract was performed. Results: GC/MS analysis revealed that the major components of N.crispa essential oil were 1,8-cineole (70.93 %), nepetalactones (5.29 %), and β-pinene (5.5 %). The volatile constituents of one of the distillates resemble the essential oil of N. crispa. The extract from aerial parts of N. crispa consistently exhibited more anti-oxidative power than its essential oil with an IC50 of 2.792 ± 0.385 mg/ml. The results from assays for total phenols and flavonoids revealed that this plant possesses phenolic and flavonoid content of 69.24 ± 3.34 µg GAEs/mg and 12.01 ± 0.26 µg QEs/mg of extract, respectively. Covering, glandular trichomes, diacytic stomata, and spiral vessels were seen in microscopic studies. Conclusion: Our results suggest that N. crispa possess considerable anti-oxidative potential with relatively high phenolic and flavonoid content in which 1,8-cineole is the major component. Due to the rarity of this plant, there are fraudulent specimens among its commercial distillates.